Pemeriksaan Pajak dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak (Studi Pada Restoran di Kabupaten Grobogan) - Widaryanti Widaryanti; Panca Wahyuningsih (Jurnal Dinamika Ekonomi & Bisnis, 2021)
This study aims to determine whether tax audits and tax sanctions affect taxpayer compliance at BPPKAD Grobogan Regency. The population in this study were taxpayers registered at BPPKAD Grobogan Regency. Samples were taken as many as 76 respondents using the Probability Sampling method, namely random sampling because the sampling of members of the population was done randomly without paying attention to the existing strata and in the population. Meanwhile, data collection using a questionnaire. The results of the analysis show that the tax audit has a positive effect on the compliance of taxpayers with the t value is greater than the t table, namely 2.966> 1.665 with a significance level of 0.004 and taxation sanctions have a positive effect on the compliance of taxpayers with the t value is greater than the t table, namely 5.992> 1,665 with a significance level of 0,000.